Management of Sepsis: Recent Advancement - Patwary, Md Ismail; Bari, Mohammad Zabed Jillul; Isha, Ishrat Tahsin (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Sepsis is a systemic, deleterious host response to infection leading to acute organ dysfunction secondary to documented or suspected infection and septic shock i.e. sepsis plus hypotension not reversed with fluid resuscitation. Severe sepsis is a major healthcare problem with an extremely high mortality rate of 30-60% and it is one of the most common reasons for critically ill patients to be admitted to an intensive care unit (ICU). Excessive inflammation and coagulation and suppression of fibrinolysis are the hallmarks of Sepsis. Our medical concern is to manage sepsis and to prevent multi organ failure (MOF). Making an early, accurate diagnosis of septic shock is the key to increasing survival rates. With no specific, effective anti-sepsis therapies available, management focuses on haemodynamic stabilization and rapid resuscitation, early source control, adequate and appropriate antibiotics, organ support and modulation of the septic responses are the cornerstones of treatment. J Bangladesh Coll Phys Surg 2016; 34(4): 206-212